Pelatihan Desain PLTS Berbasis Software Helioscope Sebagai Upaya Peningkatan Kompetensi Teknis Siswa di SMK Negeri 1 Percut Sei Tuan: Penelitian - Ahmad Dani; Dino Erivianto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Helioscope-based solar power plant (PLTS) design training was conducted to improve the technical competency of students at SMK Negeri 1 Percut Sei Tuan and address the gap between the curriculum and the needs of the renewable energy industry, which requires mastery of digital tools. The training employed an educational, participatory, and demonstrative approach, with evaluation conducted through pre- and post-tests. Results showed a significant increase in knowledge, from an average of 38.5% to 87.2% (a 48.7% increase), exceeding the 30% target. All participants completed the household solar power plant design assignment, and 97.1% were able to perform basic tasks such as creating new projects and inputting location data. Participant feedback was very positive, with 74.3%–88.6% rating all aspects of the training as “Very Good” or “Good,” particularly instructor competence (88.6%). This training effectively bridges the gap between vocational education and Industry 4.0, enhancing the competitiveness of vocational high school graduates in the renewable energy sector. Its long-term impact has the potential to support the integration of software-based learning into the curriculum, the establishment of renewable energy clubs, and industry partnerships. This training has proven effective in preparing competent workers in the renewable energy sector.